The Role of Urban Wastewater in the Environmental Transmission of Antimicrobial Resistance: The Current Situation in Italy (2010–2019) - Triggiano, Francesco (Microorganisms, 2020)
Scientific studies show that urban wastewater treatment plants (UWWTP) are among the main sources of release of antibiotics, antibiotic resistance genes (ARG) and antibiotic-resistant bacteria (ARB) into the environment, representing a risk to human health. This review summarizes selected publications from 1 January 2010 to 31 December 2019, with particular attention to the presence and treatment of ARG and ARB in UWWTPs in Italy. Following a brief introduction, the review is divided into three sections: (i) phenotypic assessment (ARB) and (ii) genotypic assessment (ARG) of resistant microorganisms, and (iii) wastewater treatment processes. Each article was read entirely to extract the year of publication, the geographical area of the UWWTP, the ARB and ARG found, and the type of disinfection treatment used. Among the ARB, we focused on the antibiotic resistance of Escherichia coli, Klebsiella pneumoniae, and Enterococci in UWWTP. The results show that the information presented in the literature to date is not exhaustive; therefore, future scientific studies at the national level are needed to better understand the spread of ARB and ARG, and also to develop new treatment methods to reduce this spread.